1975
DOI: 10.1161/01.cir.52.5.854
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of myocardial O2 supply due to hyperventilation.

Abstract: SUMMARYThirteen patients with ischemic coronary heart disease purposely hyperventilated for seven minutes in order to induce hypocapnic alkalosis. One patient experienced chest pain, and one exhibited chemical signs of myocardial hypoxia. Heart rate, blood pressure and myocardial 02 consumption did not change significantly. Coronary blood flow decreased and coronary (a-v)O2 difference widened. Since the alkalosis increased the blood 02 affinity, the fall in Po2 in coronary venous blood was proportionately even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

1978
1978
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(34 citation statements)
references
References 22 publications
0
32
1
1
Order By: Relevance
“…Assessment of cardiac inpatients was conducted at the patients' bedside. We decided not to conduct a hyperventilation provocation test with cardiac inpatients, because prolonged hyperventilation may impair myocardial oxygen supply and cause other potentially harmful effects in patients with serious heart disease such as coronary vasoconstriction and microspasms (Neill and Hattenhauer, 1975). Postoperative inpatients in the surgical wards who had agreed to participate completed questionnaires in their hospital room.…”
Section: Methodsmentioning
confidence: 99%
“…Assessment of cardiac inpatients was conducted at the patients' bedside. We decided not to conduct a hyperventilation provocation test with cardiac inpatients, because prolonged hyperventilation may impair myocardial oxygen supply and cause other potentially harmful effects in patients with serious heart disease such as coronary vasoconstriction and microspasms (Neill and Hattenhauer, 1975). Postoperative inpatients in the surgical wards who had agreed to participate completed questionnaires in their hospital room.…”
Section: Methodsmentioning
confidence: 99%
“…It could therefore pose a risk to patients with ischemic heart disease. Several studies have shown that voluntary hyperventilation in patients with ischemic heart disease can produce mean arterial pH values of as high as 7.58 (H + concentration 26 nmol/L) and ischemic changes in the electrocardiogram (50,51). However, coronary artery constriction does not occur (51) and the ECG changes may be due to potassium fluxes and autonomic nervous system activity rather than alkalemia (52).…”
Section: Coronary Vasoconstrictionmentioning
confidence: 99%
“…Am increased myocardial ateriovenous oxygen difference without or with only a minor reduction in myocardial blood flow (MBF) has been demonstrated during hypocapnia (Case et al 1975;Ekrrhart and Smith 1988;Neill and Hattenhauer 1975;Wexels et al 1985). It has been proposed that the absence of a significant reduction in MBF during hypocapnia has been a result of an opposing coronary vasodilating force caused by impaired myocardial oxygen supply (Case et al 1975;Neill and Hattenhauer 1975;Wexels et al 1985).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that the absence of a significant reduction in MBF during hypocapnia has been a result of an opposing coronary vasodilating force caused by impaired myocardial oxygen supply (Case et al 1975;Neill and Hattenhauer 1975;Wexels et al 1985). The first part of the present study was carried out to examine whether a maximal decline in coronary sinus (CS) oxygen content was reached during h y p a p n i a , inhibiting further coronary vasoconstriction.…”
Section: Introductionmentioning
confidence: 99%